Thermal behavior of some cyclic anhydrides: an important characterization for synthesis in the polymer field - Gaglieri, Caroline [UNESP]; de Moura, Aniele [UNESP]; Alarcon, Rafael T. [UNESP]; Magri, Raquel [UNESP]; Bannach, Gilbert [UNESP] (Springer Nature, 2022)
Polyfunctional cyclic organic anhydrides are widely used in different fields, especially in monomer synthesis and therefore polymers applications. However, there is a lack in the literature about their thermal and spectroscopic characterization, which can lead researchers to a misunderstanding result, interpretation, and even spoiling yield values when there is a mixture between anhydride and its respective acid. Thus, in the present paper, it was evaluated a complete and depth thermal and spectroscopic characterization of some anhydrides (maleic, succinic, phthalic, naphthalic, pyromellitic, and benzophenone). In addition, it was demonstrated how to identify the acid presence, and how to recovery the anhydride (when possible) by thermal analysis. Lastly, it was demonstrated case studies about the importance of knowing the anhydrides properties to verify residual anhydrides in final products, anhydrides recovering as well as parallel reactions in polymer synthesis using some organocatalysts. Furthermore, UV–vis results exhibited absorption bands for each anhydride, which can be helpful for researches about aggregation-induced emission observed in some luminescent materials.
Keywords: Anhydrides decomposition; Aromatic anhydrides; Crosslinkers; Dianhydrides; Thermal recuperation